A cold highland wind [large type] - Alexander, Tasha, 1969- (Alexander, Tasha, 1969- Lady Emily mystery., 2024)
"In this new installment of Tasha Alexander's acclaimed Lady Emily series set in the wild Scottish highlands, an ancient story of witchcraft may hold the key to solving a murder centuries later. In the summer of 1905, Lady Emily, husband Colin Hargreaves, and their three sons eagerly embark on a family vacation at Cairnfarn Castle, the Scottish estate of their dear friend Jeremy, Duke of Bainbridge. But a high-spirited celebration at the beginning of their stay comes to a grisly end when the duke's gamekeeper is found murdered on the banks of the loch. Handsome Angus Sinclair had a host of enemies: the fiancée he abandoned in Edinburgh, the young woman who had fallen hopelessly in love with him, and the rough farmer who saw him as a rival for her affections. But what is the meaning of the curious runic stone left on Sinclair's forehead? Clues may be found in the story of Lady MacAllister, wife of the Laird of Cairnfarn Castle, who in 1676 suddenly found herself widowed and thrown out of her home. Her sole companion was a Moorish slave girl who helped her secretly spirit her most prized possessions--a collection of strange books--out of the castle. When her neighbors, wary of a woman living on her own, found a poppet--a doll used to cast spells--and a daisy wheel in her isolated cottage, Lady MacAllister was accused of witchcraft, a crime punishable by death. Hundreds of years later, Lady Emily searches for the link between Lady MacAllister's harrowing witchcraft trial and the brutal death of Sinclair"--